Kurdology as a Western Discourse - Mohsen Ahmad Omer (پژوهشنامه ادبیات کردی)
Kurdology is a Western institutional discourse that represents Western culture and power. It is a product of the modern era. It emerged at the end of the 18th century and was mostly used at the end of the 19th century and the beginning of the 20th century. Right after the Second World War, it was used in the discourseof Oriental studies. After a period of silence, at the end of the 20th century, it reappeared in Western universities in the context of Kurdish studies. Kurdology emerged in philology, the writings of Western religious institutions, travelogues, and ethnographic studies. The Kurdish language quickly became the medium of communication between East and West but at the service of Western religious institutions. The term Kurdology first appeared in Kurdish culture in 1913, but until after the 1970s, we have no prominent Kurdish research in this area. In Kurdish sources, Kurdology is seen as a discourse in the service of Kurdish language and culture, which is a mistake due to inexperience and problems with Kurdish vision. Kurdology has always been a Western discourse and has represented a Western view, not Kurdish or Eastern.